"I Don't Want to Work in Agriculture!" The Transition from Agricultural Education to the Labor Market in Rural Russia1. (23rd September 2018) - Unay‐Gailhard, İlkay and Bavorová, Miroslava and Bednaříková, Zuzana and Ponkina, Elena V.
Abstract: In Russia, the shift in career incentives from agriculture‐related jobs to other sectors, even among agriculturally educated students, presents two main challenges to rural labor markets. The first relates to the shortage of agricultural employees. The second concerns difficulties in the school‐to‐work transition, characterized by long periods of unemployment. This article addresses these challenges by studying the career incentives of postsecondary agriculturally educated students, based on data from the Altai region, Siberia ( N = 474). We use a logit regression to predict the probability of career transition, given the incentives. We examine whether familial background and life expectations are associated with plans to pursue a career in agriculture within a life course context. The results show that students' career plans with respect to agriculture vary according to both sociofamilial background and views about one's life course.